PET modified engineering plastic for communication equipment and preparation method thereof

By adding modified talc powder and toughener to PET, the shortcomings of PET in thermal stability, impact and processing properties are solved, and its thermal stability and notch impact strength are significantly improved, and processing properties are improved, making it more effective. It can be used instead of PBT for secondary coating materials for optical fiber cables.

CN116376234BActive Publication Date: 2025-02-14SHENZHEN MPD HITECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211462826.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-02-14
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

PET engineering plastics have shortcomings in thermal stability, impact and processing properties, and it is difficult to replace the secondary coating materials used in optical fiber cables.

Method used

By adding modified talc powder and toughener to PET, the nucleation method of PET is changed, its thermal stability and impact are improved, and processing performance is improved.

Benefits of technology

The thermal stability and notch impact strength of PET modified engineering plastics are significantly improved, and their processing performance is improved, allowing them to replace PBT for secondary coating materials for fiber optic cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004259312560000021
    Figure GDA0004259312560000021
  • Figure GDA0004259312560000061
    Figure GDA0004259312560000061
  • Figure GDA0004259312560000062
    Figure GDA0004259312560000062
Patent Text Reader

Abstract

The present application relates to the technical field of PET materials, and specifically discloses a PET modified engineering plastic for communication equipment and a preparation method thereof. A PET modified engineering plastic for communication equipment is made of the following raw materials in percentage by weight: PET, modified talcum powder, toughening agent and antioxidant; the present invention improves the thermal stability and impact resistance of PET and improves the processability of PET by adding modified talcum powder and toughening agent to PET. The modified talcum powder selected in the present application has a strong nucleation effect, which can effectively change the nucleation mode of PET, reduce the crystallization temperature of PET, and also improve the thermal stability of PET engineering plastics. The compounding of modified talcum powder and toughening agent greatly improves the notched impact strength of PET engineering plastics. In addition, the melt index of PET engineering plastics is also reduced, which improves its processing performance when applied to optical fiber cable casings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of PET engineering plastics, and more specifically, to a PET modified engineering plastic for communication equipment and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) is a thermoplastic polymer resin with good weather resistance, chemical corrosion resistance, resistance to weak acids and organic solvents, good transparency, and excellent barrier properties. It is widely used in food packaging (especially disposable beverage bottles), automobile manufacturing industry, electronic and electrical products, optical fiber coating, household appliances, high-strength fiber, textile industry and other fields, and is also one of the most widely used polymer materials. With the advent of the 5G era, the demand for optical fiber and cable will be at least 3 to 4 times that of 4G in the next three years, so there will be a higher market space for the demand for optical fiber and cable, which also means that there will be a greater demand for secondary coating materials for optical fiber and cable.

[0003] At present, domestic manufacturers generally use polybutylene terephthalate (PBT) as loose tube material, but its high price is undoubtedly a huge pressure for manufacturers. The repeating unit of PBT has only two more methylene groups than PET, and the two have similar structures, so their acid and alkali resistance, softness, elasticity and room temperature dyeing properties are very similar, but the price of PBT is 2 to 4 times that of PET. In addition, PET is inferior to PBT in thermal stability, impact resistance, processability, etc., and it is difficult to replace PBT in the secondary coating material of optical fiber and cable, which also limits the application field of PET materials.

[0004] Therefore, how to modify PET to comprehensively improve the thermal stability, impact resistance and processing performance of PET materials is the key to its application in secondary coating materials for optical fiber cables, and is also the key research direction for PET modification in the future. Summary of the invention

[0005] The present invention aims at the shortcomings of PET such as poor thermal stability, impact resistance and processability, and provides a PET modified engineering plastic for communication equipment and a preparation method thereof. The present invention improves the thermal stability and impact resistance of PET and improves the processability of PET by adding modified talcum powder and a toughening agent to PET. The modified talcum powder selected in the present application has a strong nucleation effect, which can effectively change the nucleation mode of PET, reduce the crystallization temperature of PET, and also improve the thermal stability of PET engineering plastics. The modified talcum powder and the toughening agent are compounded to greatly improve the notched impact strength of PET engineering plastics. In addition, the melt index of PET engineering plastics is also reduced, which improves the processing performance when it is applied to optical fiber cable casings.

[0006] In the first aspect, the present application provides a PET modified engineering plastic for communication equipment, which adopts the following technical solution: A PET modified engineering plastic for communication equipment, which is made of the following raw materials in the following weight percentages:

[0007]

[0008]

[0009] By adopting the above technical scheme, the present application uses stearic acid to modify talcum powder and performs a modification treatment on it, so that the modified talcum powder as a filler is more closely combined with PET, and compared with ordinary talcum powder, the mechanical properties such as notched impact strength of PET engineering plastics can be greatly improved. The present application adopts modified talcum powder, toughening agent and PET to be compounded in a certain proportion, so that the prepared PET engineering plastics have good thermal stability, and at the same time effectively improve the processing performance of PET;

[0010] In addition, the present application sets a limit on the amount of modified talc added. When the amount of modified talc added is 0.5-10%, it can better improve the mechanical properties of PET engineering plastics. When the amount of modified talc added is too much, the number of modified talc particles in the PET engineering plastics also increases, dispersion becomes more difficult, and particles are prone to "agglomeration", resulting in a decrease in the tensile strength of the PET engineering plastics. Therefore, the use of modified talc within a specific range of the present application can effectively improve the mechanical properties of PET engineering plastics.

[0011] Preferably, the preparation method of the modified talc powder comprises the following steps:

[0012] S1: dissolving stearic acid (SA) in ethanol, and then stirring and heating in a water bath until the stearic acid (SA) is completely dissolved in the ethanol to form a mixed solution, and then adding talcum powder to the mixed solution, performing ultrasonic dispersion, and continuing to stir and heat to react to obtain a reaction solution;

[0013] S2: The reaction solution in S1 is cooled to room temperature and then centrifuged to obtain a precipitate, which is then placed in an oven for drying to obtain SA functionalized talc powder, i.e., modified talc powder.

[0014] By adopting the above technical scheme, during the preparation process of the modified talc, stearic acid (SA) and ethanol are first mixed, and then talc is added to the mixed solution of the two, so that the organic carboxylic acid of stearic acid can be firmly connected to the talc and is not easy to fall off; and stearic acid has more hydroxyl groups, which can effectively modify and disperse the talc, improve the compatibility and dispersibility of the modified talc in PET engineering plastics, and then greatly enhance the notched impact strength of the PET engineering plastics.

[0015] Preferably, the talcum powder comprises SiO2≥60%, MgO≥31%, CaO≤2%, and water≤0.2%.

[0016] Preferably, the talcum powder has a fineness of 5800-6200 mesh.

[0017] Preferably, the particle size of the talc is 2.3-2.7 μm.

[0018] By adopting the above technical scheme, generally speaking, the surface of talcum powder has more active functional groups, which makes the surface energy of talcum powder very large and easy to agglomerate; and the smaller the particle size of talcum powder, the higher the surface energy, and the easier it is to agglomerate during the processing, which ultimately affects the performance of filled PET engineering plastics; therefore, the present application adopts stearic acid to modify talcum powder, reduce the surface energy of talcum powder, improve the compatibility of talcum powder with PET, and make the modified talcum powder evenly dispersed in PET, so as to significantly improve the mechanical properties of PET engineering plastics.

[0019] Preferably, the toughening agent is a combination of one or more of methacrylate-acrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer and S2001 toughening agent.

[0020] Preferably, the antioxidant is one of antioxidant B900, antioxidant 168 and antioxidant 1010.

[0021] By adopting the above technical solution, the toughening agent can effectively enhance the toughness of PET engineering plastics. At the same time, the toughening agent used in this application is an organic copolymer without carbon-carbon double bonds, which can effectively increase the notched impact strength of PET engineering plastics.

[0022] In a second aspect, the present application provides a method for preparing PET modified engineering plastics for communication equipment, using the following technical solution:

[0023] A method for preparing PET modified engineering plastics for communication equipment comprises the following steps:

[0024] S1: drying PET at 110-120° C. for 4-5 hours and modified talc at 100-110° C. for 4-5 hours, and then mixing with toughening agent and antioxidant in a certain proportion to obtain a mixture;

[0025] S2: The mixed material in step S1 is melt-extruded in a twin-screw extruder and granulated to obtain PET modified engineering plastics.

[0026] By adopting the above technical scheme, the preparation method provided by the present invention is simple, and the mechanical properties of PET engineering plastics can be greatly improved through the compounding of various preparation raw materials. In addition, the present application effectively improves the processing performance of PET.

[0027] In a third aspect, the present application provides an application of PET modified engineering plastics for communication equipment in optical fiber cable casings.

[0028] In summary, this application has the following obvious advantages:

[0029] 1. The present application adopts modified talcum powder, toughening agent and PET to be compounded in a certain ratio, so that the thermal stability of the prepared PET modified engineering plastic is greatly improved. At the same time, the addition of the toughening agent can inhibit the increase of PET melt fluidity caused by the addition of modified talcum powder. The synergistic effect of the two can effectively improve the processing performance of PET;

[0030] 2. The present application sets a limit on the amount of modified talc added. When the amount of modified talc added is 0.5-10%, it can better improve the mechanical properties of PET engineering plastics. When the amount of modified talc added is too much, the number of modified talc particles in PET engineering plastics also increases, dispersion becomes more difficult, and it is easy to agglomerate, resulting in a decrease in the tensile strength of PET engineering plastics. The use of modified talc within a specific range of the present application can effectively improve the mechanical properties of PET engineering plastics. 3. The organic carboxylic acid of stearic acid can be firmly connected to talc and is not easy to fall off. Stearic acid has more hydroxyl groups, which can effectively modify and disperse talc, improve the compatibility and dispersibility of modified talc in PET engineering plastics, and thus improve the notched impact strength and thermal stability of PET engineering plastics. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a macroscopic schematic diagram of Comparative Example 5(a) and Example 1(b) in the present application; and Example 2(c) after being heated at 120°C for 3h. DETAILED DESCRIPTION

[0032] The present application is further described in detail below with reference to the accompanying drawings and examples. It is specially noted that if no specific conditions are specified in the following examples, the conventional conditions or the conditions recommended by the manufacturer are followed, and the raw materials used in the following examples can be obtained from common commercial sources unless otherwise specified.

[0033] Preparation Example

[0034] Preparation Example 1

[0035] The preparation of modified talcum powder comprises the following steps:

[0036] S1. Dissolve 100 parts of stearic acid (SA) in a reaction bottle containing 500 ml of ethanol, then put the reaction bottle into a water bath, stir and heat at 90° C. in the water bath until the stearic acid (SA) is completely dissolved in the ethanol to form a mixed solution, then add 200 parts of talc to the mixed solution for ultrasonic dispersion for 20 minutes, and continue to stir and heat at 90° C. in a water bath for 6 hours to obtain a reaction solution;

[0037] S2. The reaction solution in S1 is cooled to room temperature and then centrifuged to obtain a precipitate, which is then dried in an oven at 80° C. for 24 hours. After drying, the precipitate is crushed into powder using a pulverizer to obtain SA functionalized talc powder, i.e., modified talc powder.

[0038] The talc powder used in this preparation example has the following components: SiO2≥60%, MgO≥31%, CaO≤2%, water≤0.2%, and the talc powder has a fineness of 6200 mesh and a particle size of 2.3 μm.

[0039] In other preparation examples, the fineness of the talc powder can also be selected to be 5800-6200 mesh, and the particle size can also be selected to be 2.3-2.7 μm.

[0040] Example

[0041] Example 1

[0042] A method for preparing PET modified engineering plastics for communication equipment comprises the following steps:

[0043] S1: drying PET at 120° C. for 4 h, and drying modified talc at 100° C. for 4 h, and then mixing them in a blender in a ratio of PET: modified talc: antioxidant: toughening agent = 84.6:10:0.4:5 to obtain a mixture;

[0044] S2: Melting and extruding the mixed material in step S1 in a twin-screw extruder, and pelletizing in a pelletizer to obtain PET modified engineering plastics;

[0045] Among them, the modified talc powder used in the examples of the present application is the modified talc powder prepared in Preparation Example 1, the toughening agent is S2001 toughening agent, and the antioxidant is antioxidant B900.

[0046] Example 2

[0047] A method for preparing PET modified engineering plastics for communication equipment comprises the following steps:

[0048] S1: drying PET at 120° C. for 4 h, drying modified talc at 100° C. for 4 h, and then mixing them in a blender in a ratio of PET: modified talc: antioxidant: toughening agent = 90:4.8:0.2:5 to obtain a mixture;

[0049] S2: Melting and extruding the mixed material in step S1 in a twin-screw extruder, and pelletizing in a pelletizer to obtain PET modified engineering plastics;

[0050] Among them, the modified talc powder used in the examples of the present application is the modified talc powder prepared in Preparation Example 1, the toughening agent is S2001 toughening agent, and the antioxidant is antioxidant 168.

[0051] Example 3

[0052] A method for preparing PET modified engineering plastics for communication equipment comprises the following steps:

[0053] S1: drying PET at 120° C. for 4 h, and drying modified talc at 100° C. for 4 h, and then mixing them in a blender in a ratio of PET: modified talc: antioxidant: toughening agent = 87:9.7:0.3:3 to obtain a mixed material;

[0054] S2: Melting and extruding the mixed material in step S1 in a twin-screw extruder, and pelletizing in a pelletizer to obtain PET modified engineering plastics;

[0055] Among them, the modified talc powder used in the examples of the present application is the modified talc powder prepared in Preparation Example 1, the toughening agent is S2001 toughening agent, and the antioxidant is antioxidant 1010.

[0056] Example 4

[0057] A method for preparing PET modified engineering plastics for communication equipment comprises the following steps:

[0058] S1: drying PET at 120° C. for 4 h, and drying modified talc at 100° C. for 4 h, and then mixing them in a blender in a ratio of PET: modified talc: antioxidant: toughening agent = 94.1:0.5:0.4:5 to obtain a mixture;

[0059] S2: Melting and extruding the mixed material in step S1 in a twin-screw extruder, and pelletizing in a pelletizer to obtain PET modified engineering plastics;

[0060] Among them, the modified talc powder used in the examples of the present application is the modified talc powder prepared in Preparation Example 1, the toughening agent is S2001 toughening agent, and the antioxidant is antioxidant 1010.

[0061] Example 5

[0062] A method for preparing PET modified engineering plastics for communication equipment comprises the following steps:

[0063] S1: drying PET at 120° C. for 4 h, and drying modified talc at 100° C. for 4 h, and then mixing them in a blender in a ratio of PET: modified talc: antioxidant: toughening agent = 90:5:0.4:4.6 to obtain a mixture;

[0064] S2: Melting and extruding the mixed material in step S1 in a twin-screw extruder, and pelletizing in a pelletizer to obtain PET modified engineering plastics;

[0065] Among them, the modified talc powder used in the examples of the present application is the modified talc powder prepared in Preparation Example 1, the toughening agent is S2001 toughening agent, and the antioxidant is antioxidant 1010.

[0066] Table 1: Component ratio of PET modified engineering plastics in Examples 1-5

[0067]

[0068] Comparative Example

[0069] Comparative Example 1

[0070] A method for preparing PET modified engineering plastics for communication equipment comprises the following steps:

[0071] S1: drying PET at 120° C. for 4 h, drying talc at 100° C. for 4 h, and then mixing them in a blender in a ratio of PET: talc: antioxidant: toughening agent = 87:9.7:0.3:3 to obtain a mixed material;

[0072] S2: melt-extrude the mixture in step S1 in a twin-screw extruder, and granulate it in a pelletizer to obtain PET engineering plastic; wherein the talcum powder used in the comparative example of the present application is ordinary talcum powder without modification, the toughening agent is S2001 toughening agent, and the antioxidant is antioxidant 1010.

[0073] Table 2: Component ratio of PET modified engineering plastics in Comparative Examples 1-5

[0074]

[0075] Among them, the toughening agent used in Comparative Example 4 is MBS toughening agent.

[0076] Performance testing

[0077] The following performance tests were performed on the PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5. The specific test data are shown in Table 3:

[0078] Glass transition temperature: The glass transition temperature of the PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T22567-2008;

[0079] Crystallization temperature: The PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 were tested for crystallization temperature according to GB / T19466.3-2004;

[0080] Melting temperature: The melting temperature of the PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T16582-2008;

[0081] Melt index: The melt index of the PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T3682;

[0082] Notched impact strength: The notched impact strength of the PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T1843;

[0083] Tensile strength: The tensile strength of the PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T1040.

[0084] Thermal shrinkage test: The PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 were injection molded into standard specimens with a length of 8±0.1 cm, a width of 1±0.1 cm, and a thickness of 0.40±0.1 cm. The specimens were placed at 120°C for 3 hours, cooled, and the length changes before and after were tested, and the thermal shrinkage rate was calculated. The calculation formula is as follows:

[0085] β=(L0-L s ) / L0

[0086] Where L0 is the original length of the sample, and Ls is the length of the sample after heating and cooling.

[0087] Table 3: Test data of PET modified engineering plastics in Examples 1-5 and Comparative Examples 1-5

[0088]

[0089]

[0090] Thermal stability: The PET modified engineering plastics prepared in Examples 1-5 and Comparative Examples 1-5 were heated at 120° C. for 3 h, and their shrinkage rates were tested respectively. The specific test data are shown in Table 4.

[0091] Table 4: Test data of PET modified engineering plastics in Examples 1-5 and Comparative Examples 1-5

[0092]

[0093] Combined with Examples 1-5 and Comparative Example 5 and Table 3 and Figure 1 It can be seen that after adding a certain proportion of modified talc to PET, the glass transition temperature and melting temperature of Examples 1-5 tend to be slightly increased, and the thermal shrinkage rate is also reduced by more than 40%. After heating at 120°C for 3h, the PET modified engineering plastics can hardly be seen to have much deformation from a macroscopic perspective, while the PET of Comparative Example 5 has a larger deformation. Therefore, the thermal stability of the modified PET engineering plastics is effectively improved.

[0094] In addition, it is clearly found that the crystallization temperature of Examples 1-5 is significantly reduced, and the modified talc has a strong nucleation effect, which can effectively change the nucleation mode of PET. The use of modified talc and toughening agent in combination can effectively improve the notched impact strength of PET modified plastics. Although the tensile strength of Examples 4-5 is reduced, the reduction is not obvious, while the notched impact strength is greatly improved, indicating that the toughness of PET modified engineering plastics is greatly improved.

[0095] Combining Example 3 and Comparative Examples 1-2 and Table 3 and Table 4, it can be seen that no modified talcum powder is added to Comparative Example 2, and therefore, the thermal shrinkage of the PET engineering plastic in Comparative Example 2 is not improved, indicating that the temperature resistance is deteriorated and the crystallization temperature is high; ordinary talcum powder is added to Comparative Example 1, and its notched impact strength is slightly improved, and the degree of improvement in thermal shrinkage is small, but it is not obvious compared with the improvement in Example 3.

[0096] Through Example 3, Comparative Examples 1, 2, 3, 4 and Comparative Example 5, it is found that the addition of modified or unmodified talcum powder will increase the melt index of the PET system and the fluidity, which is very unfavorable for the molding of the sleeve during the processing of optical fiber cables; from Example 3, Comparative Example 3 and Comparative Example 4, it can be seen that MBS toughening agent is added to Comparative Example 4, and the molecular structure of MBS toughening agent contains butadiene and has a carbon-carbon double bond unsaturated structure, which can slightly improve the notched impact strength of PET engineering plastics, but it is not obvious, and has no effect on the melt index, and the toughening agent selected by the patent of the present invention can not only greatly improve the notched impact strength of PET, but also reduce the melt index of the system and improve the processing performance of modified PET in optical fiber cable sleeves. Therefore, the toughening agent without carbon-carbon double bonds used in this application can be compounded with other raw materials in a certain proportion, and the prepared PET modified engineering plastics can not only improve the thermal stability of PET, but also improve the mechanical properties, and also have good processing performance.

[0097] In addition, no toughening agent is added in Comparative Example 3, and its notched impact strength is lower than that of Comparative Example 5, but its tensile strength is higher than that of Comparative Example 5, and the melt index of the modified PET engineering plastic of Comparative Example 3 is large, which is not conducive to the processing and molding of optical fiber cables; no modified talcum powder is added in Comparative Example 2, and the notched impact strength is higher than that of Comparative Example 5, but the tensile strength is reduced, and the melt index of Comparative Example 2 is significantly reduced, which is conducive to processing and molding; this shows that the addition of modified talcum powder improves the tensile strength, but reduces the notched impact strength, and the melt index of the prepared modified PET is large, which is not conducive to processing and molding; the toughening agent used in the present application has the effect of greatly improving the notched impact strength and reducing the melt index at the same time, therefore, the toughening agent without carbon-carbon double bonds is compounded with the modified talcum powder, and the two act synergistically, and the toughening agent makes up for the defects of increased melt index and reduced notched impact caused by the modified talcum powder, so that the notched impact strength of the prepared modified PET engineering plastic is greatly improved, and the processing performance is greatly improved.

[0098] In summary, the thermal stability of the PET modified engineering plastics prepared in the present application is greatly improved, the notched impact strength is greatly improved, and the processing performance is greatly improved, and it can be used to replace PBT as a secondary coating material for optical fiber cables.

[0099] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A PET modified engineering plastic for communication equipment, characterized in that: Made from the following raw materials in weight percentage: PET 90~94.1%; Modified talc 0.5~5%; Toughener 4.6-5%, wherein the toughener is S2001 toughener; Antioxidant 0.2~0.4%; The preparation method of the modified talcum powder comprises the following steps: S1: dissolving stearic acid in ethanol, and then stirring and heating in a water bath until the stearic acid is completely dissolved in the ethanol to form a mixed solution, and then adding talcum powder to the mixed solution, performing ultrasonic dispersion, and continuing to stir and heat to react to obtain a reaction solution; S2: Cooling the reaction solution in S1 to room temperature and then centrifuging to obtain a precipitate, then drying the precipitate in an oven, and crushing it into powder using a grinder to obtain talc powder functionalized with stearic acid, i.e., the modified talc powder; The talcum powder comprises SiO2≥60%, MgO≥31%, CaO≤2%, and water≤0.2%; the fineness of the talcum powder is 5800-6200 mesh; and the particle size of the talcum powder is 2.3-2.7 μm.

2. A method for preparing PET modified engineering plastics for communication equipment according to claim 1, characterized in that: The following steps are involved: The PET is dried at 110-120°C for 4-5 hours, and the modified talc is dried at 100-110°C for 4-5 hours, and then mixed with a toughening agent and an antioxidant in a certain proportion and stirred evenly to obtain a mixture; The mixed material is melt-extruded in a twin-screw extruder and granulated to obtain PET modified engineering plastics.

3. Application of the PET modified engineering plastic for communication equipment as claimed in claim 1 in optical fiber cable casing.

Citation Information

Patent Citations

  • Resin composition

    JP2002161200A